Tuan Guru and the Efforts to Prevent Early Marriage Among Sasak Tribe - Sainun, Sainun; Zarkasih, Hery; Sugitanata, Arif (De Jure: Jurnal Hukum dan Syari'ah, 2024)
Early marriage is still a problem in developing countries, including Indonesia. one of the areas with a high rate of child marriage is West Nusa Tenggara. This study aims to explore the implementation of the Marriage Law Number 16 of 2019 in Rembiga Subdistrict, Mataram City, focusing on the role of Tuan Guru in reducing early marriage cases. While national trends indicate a decline, local data shows a significant increase in early marriage cases, particularly in some Indonesian provinces. The study utilised empirical legal field research and qualitative methods, involving profound observations and interviews with fourteen informants. It identified obstacles in the application of the law, including premarital pregnancy, family conflicts, economic factors, promiscuous behaviour, normative conflicts, and suboptimal socialisation. In this context, Tuan Guru plays a crucial role in fostering understanding and compliance with the law in the Sasak Rembiga community through religious studies and marriage counselling. This strategy highlights the importance of integrating religious, cultural, and legal values to minimise early marriages and calls for cross-sector collaboration for sustained effectiveness.